Immunophenotyping in BK Virus Allograft Nephropathy Distinct from Acute Rejection - Xue Li; Qiquan Sun; Jinsong Chen; Shuming Ji; Jiqiu Wen; Dongrei Cheng; Zhihong Liu (Clinical and Developmental Immunology)
Differentiating BK virus nephropathy (BKVN) from acute rejection (AR) is crucial in clinical practice, as both of them have interstitial inflammation in the grafts. The purpose of the study is to describe the inflammatory cellular constituents of BKVN and to determine the clinical utility of immunophenotyping findings in distinguishing BKVN from AR. In addition, the expression of the HLA-DR was investigated. Sixty-five renal allograft recipients were included in this study, including 22 cases of BKVN, 31 cases of AR, and 12 cases of stable allograft. Immunostaining for infiltrating lymphocytes showed that the number of CD20 cells (P<0.001) and the percentages of CD3 (P<0.001), CD4 (P=0.004), CD8 (P=0.005), and CD20 (P=0.002) cells were all significantly different between BKVN and AR. Moreover, there were no statistically significant differences in tubule cell HLA-DR expression (P=0.156). This observation suggests that the number of CD20 cells and the percentages of CD3, CD4, CD8, and CD20 cells in renal biopsies would aid the distinction between BKVN and AR. On the other hand, the presence of HLA-DR upregulation may not only be specific for acute rejection but also be a response to BKVN.